Methods of Organizing and Conducting Physical Education and Sports Events in the Daily Schedule of General Secondary School Students - Urolovich, Bobokulov Chori; Panji Ugli, Abduraimov Shakhboz (Central Asian Journal of Literature, Philosophy and Culture, 2022)
The following article discusses the methods of organizing and conducting physical education and sports events in the daily schedule of general secondary school students.